Sistem Keamanan Pada Jaringan Wireless Menggunakan Protokol RADIUS - Saputra , Aldi Sigit; Irwan, Dadan (Prodi Sistem Informasi FST Universitas Jambi, 2020)
Wireless networks require a security system to protect servers from attacks such as Port Scanning and Denial of Service. This research aims to design a wireless network security system using Remote Authentication Dial-In User Service or RADIUS protocol. The research stages include analysis of system requirements, preparation of completeness of system requirements, installation and configuration of the network and RADIUS protocol, detection and prevention testing of attacks, and analysis of test results. The design system used is to implement a single authentication, authorization, and accounting protocol that supports the internal and external networks of the Bahana Taruko Santosa Company. The results of implementing the RADIUS protocol on a wireless network server service can perform a DoS attack filter properly and block unauthorized users from accessing Internet services. Data analysis results show DoS attacks with the type of ICMP Flooding attack and UDP Flooding attack can be blocked with a percentage of 98%. In addition, there is a reduction in unauthenticated user access rights with the result of reducing the amount of bandwidth usage.